2017
DOI: 10.21037/jgo.2017.03.04
|View full text |Cite
|
Sign up to set email alerts
|

Proton beam reirradiation for locally recurrent pancreatic adenocarcinoma

Abstract: Background: Local recurrence following definitive treatment for pancreatic adenocarcinoma is common and can be associated with significant morbidity and mortality. Retreatment options for these patients are limited. Proton beam reirradiation (PRT) may limit dose and toxicity to previously irradiated normal tissues in patients without evidence of metastatic disease. PRT dose was 59.4 Gy (37.5-59.4 Gy). The median time interval from the prior treatment course was 26.7 months (7-461.3). There was a rate of 13% ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 18 publications
(44 reference statements)
0
20
0
Order By: Relevance
“…Proton beam therapy for reRT has been investigated at other disease sites including head and neck, 38,39 central nervous system, 40,41 lung, 42,43 gynecological, 44 and gastrointestinal malignancies. [45][46][47] A recent systematic review found that reRT with PBT is safe and effective. 48 Furthermore, the authors concluded that, for local recurrences, PBT might be the safest option for reRT.…”
Section: Discussionmentioning
confidence: 99%
“…Proton beam therapy for reRT has been investigated at other disease sites including head and neck, 38,39 central nervous system, 40,41 lung, 42,43 gynecological, 44 and gastrointestinal malignancies. [45][46][47] A recent systematic review found that reRT with PBT is safe and effective. 48 Furthermore, the authors concluded that, for local recurrences, PBT might be the safest option for reRT.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study of carbon-ion RT for lung cancer by Karube et al showed that the 2-year overall survival rate was 67% without severe pneumonitis (16). In abdominal tumors, the 2-year overall survival rates were 30 to 37% for proton and photon therapy (23, 25). One prospective study of proton therapy for recurrent esophageal cancer found that grade 5 esophageal fistulas and ulcers were observed in 14% of patients during the acute and late periods (22).…”
Section: Discussionmentioning
confidence: 99%
“…At a follow-up of one year, less than 10% of patients experienced serious toxicity. 35 Boimel et al 36 described auspicious results for reirradiation by PBT for locally recurrent pancreatic cancer. Proton beam therapy resulted in prolonged OS, local-regional progression-free, and DMFS, when compared to historical controls.…”
Section: Re-irradiation Of All Sites For Curative Intentmentioning
confidence: 99%